Solvability of the Dirichlet Problem for Elliptic Equations in Weighted Sobolev Spaces on Unbounded Domains. (20th August 2008) - Boccia, Serena; Monsurrò, Sara; Transirico, Maria
Abstract : This paper is concerned with the study of the Dirichlet problem for a class of second-order linear elliptic equations in weighted Sobolev spaces on unbounded domains ofℝ n, n ≥ 3 . We state a regularity result and we can deduce an existence and uniqueness theorem.